Labor force mobility – a factor of economic growth in Romania - BĂLAN, Mariana (Annals of Spiru Haret University. Economic Series, 2016)
The paper aims to identify and synthetically present some factors (demographic–economic, technologic, socio-politic, educational of cross regional disparities) which produced, at the beginning of the 21st century, a series of new migration characteristics compared to previous periods, which generated the potential for transformation of the migration processes from the point of view of the typology, level, structures, intensity, costs and benefits. Also, the paper has in view to perform a multiple analysis of labour force mobility in Romania, by regions, with the aim to identify the social and economic impact of Romanian migration.